Complications of tracheostomy in children: a systematic review - Lubianca Neto,José Faibes (2022)
Abstract Introduction: Tracheostomy is a procedure that can be associated with several well-described complications in the literature, which can be divided into transoperative, early postoperative and late postoperative. When performed in children, these risks are more common than in adults. Objective: To perform a systematic review of complications, including deaths, in tracheostomized pediatric patients. Methods: A search was carried out for articles in the Latin American and Caribbean Health Sciences Literature and PubMed databases. Cohort studies and series reports were selected, in addition to systematic reviews, published between January 1978 and June 2020, with patients up to 18 years old, and written in English, Spanish or Portuguese. Results: 1560 articles were found, of which 49 were included in this review. The average complication rate was 40%, which showed an association with age, birth weight, prematurity, comorbidities, and emergency procedures. The most common complications were cutaneous lesions and granulomas. Mortality related to the procedure reached up to 6% in children and was mainly related to cannula obstruction or accidental decannulation. Conclusion: Pediatric tracheostomy is associated with several complications. The tracheostomy-related mortality rate is low, but the overall mortality of tracheostomized patients is not negligible.